EVALUASI KESESUAIAN LAHAN UNTUK KAWASAN PERMUKIMAN DENGAN METODE MULTI CRITERIA EVALUATION DI KOTA PADANG - Iswandi Umar; Widiatmaka Widiatmaka; Bambang Pramudya; Baba Barus (Graduate School Bogor Agricultural University (SPs IPB), 2017)
Population growthis linear tothe requrement of settlement area, while the area of the earth is limited. It was caused inappropriate use of the land. This study aims to identify, analyze, and describe dynamics and suitability of land for settlements in Padang. Determination of land suitablity for settlementis using Multi Criteria Evaluation (MCE) method. The indicators used in determining the suitability of land for settlement is the slope, the frequency of flooding, drainage, distrubusi gravel, rock distribution and effective depth. Weighting in the analysis of land suitability based on the opinions of experts from various fields related to as many as 15 experts. Analysis result for land suitability of settlements in the area show that: there were 12.543 ha (18%) very suitable for settlement; 52.390 ha (75,4%) were suitable for settletment; 4.279 ha (6,2%).were compatible with marginal for settlement; and 285 ha (0,8%) were unsuitable for settlement. The area is very suitable for residential areas is very limited, so expect optimal utilization.